Total serum IgE levels among adults patients with intermittent and persistent allergic asthmas (Medical Journal of Indonesia, 2018)
Background: Obesity with knee osteoarthritis (OA) is related to chronic pain causing physical inactivity that leads to decreased cardiorespiratory endurance and quality of life. Aquatic and land-based exercises are effective in improving physical activity. The aim of this study is to compare between aquatic and land-based exercise to improve cardiorespiratory endurance and quality of life in obese patients with knee osteoarthritis.Methods: A single-blind, randomized, controlled trial was conducted on thirty-three obese patients with knee OA who visited Obesity Clinic of Medical Rehabilitation Cipto Mangunkusumo Hospital, from October 2016 to January 2017, subjects were divided into aquatic or land-based exercise group. Aerobic and knee-strengthening exercises were given. Cardiorespiratory endurance was assessed using the Borg Scale, whereas both the BORG CR-10 and SF-36 questionnaires were used to assess quality of life.Results: After intervention, there were significant improvements in the land-based exercise group in the rating of perceived exertion (p=0.02), role limitations due to physical health (p=0.024), role limitations due to emotional problems (p=0.041), energy/fatigue (p=0.016), and the decline in pain (p=0.049) parameters. While in the aquatic exercise, there were significant improvements in leg fatigue (p=0.016), energy/fatigue (p=0.025), emotional well-being (p<0.001), and general health (p=0.045) parameters. Despite this, there were no significant differences between two groups regarding cardiorespiratory endurance and quality of life.Conclusion: This study found that patients could start aquatic exercise to reduce leg fatigue and enhance general health and energy. After that, exercise could be continued in land-based settings to improve cardiorespiratory endurance and quality of life.